First report of predation by a stink bug (Supputius cincticeps Stål) on a walking-stick insect (Cladomorphus phyllinus Gray), with reflections on evolutionary mechanisms for camouflage - Costa, outros, Jane (Acta Biológica Paranaense, 2019)
OBJECTIVE — The stink bug Supputius cincticeps is a well-known neotropical, generalist predator. However, in contrast to other predators, S. cincticeps also need to feed on plants to complete its life cycle. The aim of this report is to describe predation by S. cincticeps on Cladomorphus phyllinus, a walking-stick insect that feeds on leaves of several fruit trees, and is considered one of the largest walk-stick insect species in the Southern Hemisphere. Also a new hypothesis for camouflage is discussed. RESULTS — Suputius cincticeps, recently brought from nature, was accidentally introduced into a colony of C. phyllinus, while feeding them with guava leaves. Once the nymph of S. cincticeps detected the C. phyllinus female it displayed immediately feeding behavior. Both adults and nymphs of C. phyllinus were observed to be predated by S. cincticeps. This new predatory interaction offers a novel evolutionary hypothesis for camouflage based on horizontal transfer of genes a process that might be occurring in nature.